2017
DOI: 10.1007/s00408-017-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity on Reporting of Childhood Asthma Symptoms

Abstract: This study aims to determine the impact of physical activity on asthma symptom reporting among children living in an inner city. Among 147 children aged 5–12 years with physician-diagnosed asthma, we assessed asthma symptoms using twice-daily diaries and physical activity using the physical activity questionnaire for children during three 8-day periods (baseline, 3 and 6 months). Linear, logistic, and quasi-poisson regression models were used to determine the association between physical activity and asthma sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…In another study, it was found that those who were physically active were also more inclined to report symptoms of asthma during the day and night awakenings. ( 13 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, it was found that those who were physically active were also more inclined to report symptoms of asthma during the day and night awakenings. ( 13 )…”
Section: Discussionmentioning
confidence: 99%
“…( 11 ) However, scientific production regarding the relation between the levels of physical activity and asthma control in children and adolescents is still scarce, and the existing results are controversial. ( 12 , 13 )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the relationship between asthma and physical activity have shown conflicting results. In a longitudinal study of 147 children aged 5-12 years of age in Baltimore, MD, Nnodum et al 34 found a significant association between physical activity, as measured by the physical activity questionnaire, and an increased frequency of asthma symptoms. These results suggest that children may be more bothered by their asthma when engaged in higher levels of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…albuterol) use were assessed using a pediatric asthma diary, 47 a validated daily questionnaire completed by the caregiver twice daily over the one-week period of each study visit as previously described. 48 Daytime symptoms were measured on a 6-point Likert scale and were dichotomized into being absent or present, with composite daytime symptoms representing none vs. any positive response across the three daily symptoms. Nighttime symptoms included an assessment of the number of awakenings caused by asthma symptoms on a 4-point Likert scale, dichotomized into being absent or present.…”
Section: Methodsmentioning
confidence: 99%